Chapter Латинский перевод Томаса Консетта Грамматики М. Смотрицкого (1648 г.). История одного перевода - Celbaeva, Tat’jana (Firenze University Press, 2025)
Thomas Consett's Latin Translation of M. Smotritsky's Grammar (1648): The History of a Translation. The following article presents the Latin translation of M. Smotrytsky’s grammar (as printed 1648) by Thomas Consett. Consett, an English priest and missionary who spent ca. 10 years of his live in Russia, wrote this translation in the first third of the 18th century. The translation as well as further “Russian” books owned by Consett are being kept in the archives of the Francke-Foundations in Halle and are interesting for scientific researchers as many of them are unique and yet not deeply investigated.